ADSORPTION OF FERROUS IONS ONTO BACILLUS SUBTILIS CELLS - Châtellier X.; Fortin D. (My University, 2004)
Secondary iron-oxides forming by the oxidation of ferrous ions have been observed to accumulate on the surface of bacterial cells in various environments (e.g. lake sediments). It is not always clear to which extent the presence of the bacteria can affect the precipitation process. The cells may play an active (metabolic) role in the oxidation of the ferrous ions. Whether this is the case or not, it does not change the fact that bacterial surfaces can also sorb ferrous/ferric ions and crystal nuclei and therefore influence the properties of the Fe-rich crystals. In order to determine the relative roles of active and passive processes, an important step is to quantify the interactions between ferrous ions and bacterial surfaces. We have measured the kinetics of adsorption and the pH-adsorption/desorption isotherms of ferrous ions on the surface of Bacillus subtilis cells under anaerobic conditions, using various sorbent/sorbate ratios. In conjunction with pH-titrations, this allowed us to estimate the adsorption constants of the ferrous ions onto the various chemical sites that are present on the surface of the cells (e.g. -log(K) ~3.45 for the carboxylic groups). We find that the adsorption of the ferrous ions is a quick but reversible process, which can be modeled by statistical thermodynamics. We will describe our results and discuss their consequences in the example of a simple experience of biomineralization realized in the laboratory with Bacillus subtilis cells.